LIMNOLOGICAL STUDY OF PRANTIJ BOKH, DIST: SABARKANTHA, GUJARAT (International Association of Biologicals and Computational Digest, 2022)
Changes in water chemistry and algal composition of different sites of Prantij Bokh, which is an irrigation tank, are correlated in the present communication. Season wise analysis of water chemistry was carried out during different seasons and algal flora occurring during three seasons i.e. Monsoon, Winter and Summer were correlated with changes in water chemistry with changing season both water chemistry and algal composition also changed. Water samples of the Bokh were examined for various physico-chemical parameters as pH, Total Hardness, Chloride, Carbonates, Bicarbonates, Calcium and Magnesium Contents, Calcium and Magnesium Hardness, Alkalinity and Electric Conductivity (EC) etc. by standard international methods algae were identified by repeatedly making slides and Camera Lucida drawing were also made. Standard monographs were referred for confirming identification of algae.
Keywords: Bokh water analysis, algal analysis, physico-chemical parameters and correlation between them of Prantij Bokh, Dist: Sabarkantha, Gujarat State.